Building a knowledge-intensive medical device industry: the effect of knowledge creation in R&D project performance - Yee, Yann Mey; Tan, Cheng Ling; Aizzat Mohd. Nasurdin; Yeo, Sook Fern; Thurasamy Ramayah (Penerbit Universiti Kebangsaan Malaysia, 2020)
This study aimed to examine the influence of the organizational factors (reward, training, and collaboration) and knowledge creation process on R&D project performance. A quantitative approach was employed with the data obtained from the sample of R&D projects from the medical device firms listed on the Association of Malaysian Medical Industries (AAMI). Smart-PLS 3.0 software was used to check the data validity and reliability, and to test the structural path modeling. A total of 115 R&D project managers participated in this study with a response rate of 27.2%. The results revealed that six sub-hypotheses out of seven sub-hypotheses were supported. Based on the findings, this study implies that organizational factors, such as reward and collaboration, with the knowledge creation process as the mediator, are critical to enhance the R&D project performance among medical devices firms. This study provides theoretical and practical implications as well as suggestions for future R&D performance studies in different industries.